VIEWS OF CLASSIC UZBEK SCHOLARS ON THE DEVELOPMENT OF THE CIVIL SERVICE INSTITUTE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the article, the requirements for civil servants are analyzed in national-historical sources, in particular, "Avesta", as well as the ideas contained in the works of Abu Nasr Farabi, Yusuf Khos Hajib, Nizamulmulk, Amir Temur, Alisher Navoi. Based on these ideas, ideas about the possibility of improving the public service have been put forward even today.